The Cabling Handbook - Vacca,John (Prentice Hall PTR, 1999)
Comprehensive guide to every aspect of LAN & telecommunications cabling, from planning through installation & management. Paper. DLC: Telecommunications wiring - Handbooks, manuals, etc.